Fix-it and forget it budget meals : quick easy & inexpensive slow cooker and instant pot recipes - Comerford, Hope (Fix-it and forget-it (Good Books (Intercourse, Pa.)), 2024)
Looking for quick and easy meals that are also shockingly affordable? You've come to the right place. There's no need to spend a fortune on ingredients. Hope Comerford has compiled more than 100 recipes that are delicious, family-friendly, and cheap!